Fathering, parental leave, impacts, and gender equality: what/how are we measuring?. Issue 5 (10th March 2020) - Doucet, Andrea; McKay, Lindsey
Abstract : Purpose: This research article explores several questions about assessing the impacts of fathers' parental leave take up and gender equality. We ask: How does the conceptual and contextual specificity of care and equality shape what we focus on, and how, when we study parental leave policies and their impacts? What and how are we measuring? Design/methodology/approach: The article is based on a longitudinal qualitative research study on families with fathers who had taken parental leave in two Canadian provinces (Ontario and Québec), which included interviews with 26 couples in the first stage (25 mother/father couples and one father/father couple) and with nine couples a decade later. Guided by Margaret Somers' historical sociology of concept formation, we explore the concepts of care and equality (and their histories, networks, and narratives) and how they are taken up in parental leave research. We also draw on insights from three feminist scholars who have made major contributions to theoretical intersections between care, work, equality, social protection policies, and care deficits: Nancy Fraser, Joan Williams, and Martha Fineman. Findings: The relationship between fathers' leave-taking and gender equality impacts is a complex, non-linear entanglement shaped by the specificities of state and employment policies and by how these structure parental eligibility for leave benefits, financial dimensions of leave-taking (including wage replacement rates for benefits), childcare possibilities/limitations and related financial dimensions for families, masculine work norms in workplaces, and intersections of gender and social class. Overall, we found that maximizing both parental leave time and family income in order to sustain good care for their children (through paid and unpaid leave time, followed by limited and expensive childcare services) was articulated as a more immediate concern to parents than were issues of gender equality. Our research supports the need to draw closer connections between parental leave, childcare, and workplace policies to better understand how these all shape parental leave decisions and practices and possible gender equality outcomes. Research limitations/implications: The article is based on a small and fairly homogenous Canadian research sample and thus calls for more research to be done on diverse families, with attention to possible conceptual diversity arising from these sites. Practical implications: This research calls for greater attention to: the genealogies of, and relations between, the concepts of care, equality, and subjectivity that guide parental leave research and policy; to the historical specificity of models like the Universal Caregiver model; and to the need for new models and conceptual configurations that can guide research on care, equality, and parental leave policies in current global contexts of neoliberal capitalism. Originality/value: We call for a move toward thinking about care, not only as care time, but as responsibilities, which can be partly assessed through the stories people tell about how they negotiate and navigate care, domestic work, and paid work responsibilities in specific contexts and conditions across time. We also advocate for gender equality concepts that attend to how families navigate restrictive parental leave and childcare policies and how broader socio-economic inequalities arise partly from state policies underpinned by a concept of liberal autonomous subjects rather than relational subjects who face moments of vulnerability and inter-dependence across the life course.